2004
DOI: 10.1016/j.femsec.2004.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Detection and widespread distribution of the nrfA gene encoding nitrite reduction to ammonia, a short circuit in the biological nitrogen cycle that competes with denitrification

Abstract: Degenerate primers to detect nrfA were designed by aligning six nrfA sequences including Escherichia coli K-12, Sulfurospirillum deleyianum and Wolinella succinogenes. These primers amplified a 490 bp fragment of nrfA. The ability of these primers to detect nrfA was tested with chromosomal DNA isolated from a variety of bacteria: they could distinguish between bacteria in which the gene is known to be present or absent. The positive reference organisms spanned the various classes of Proteobacteria, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
112
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(113 citation statements)
references
References 35 publications
0
112
0
1
Order By: Relevance
“…4). Future studies will concentrate on the mechanism of nitrite reduction (14) and propionate oxidation via biochemical assays, as has been described for other bacteria (24,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Future studies will concentrate on the mechanism of nitrite reduction (14) and propionate oxidation via biochemical assays, as has been described for other bacteria (24,30).…”
Section: Discussionmentioning
confidence: 99%
“…Carbon dioxide was measured on an HP6890 gas chromatograph (80°C; poropack Q in combination with a 5-Å molsieve) equipped with a thermal conductivity detector. The bacterial population was monitored by FISH and immunofluorescence analysis as described previously (13,14,20). The oligonucleotide probes applied were as follows: AMX368 [S-G-Amx-0368-a-A-22] covering all anammox organisms, PLA46 [S-P-Planc-0046-a-A-18] covering all Planctomycetes, EUB338 mix [S-DBact-0338-a-A-18] covering almost all Bacteria, ALFA968 [S-P-Alph-968-a-A-18] covering most Alphaproteobacteria, BET42a [L-P-Beta-1027-a-A-17] covering most Betaproteobacteria, and GAM42a [L-P-Gamm-1027-a-A-17] covering most Gammaproteobacteria (11).…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplifications were carried out as previously described. All the primers used in this study were fully characterised in previous studies, in which they were used as primers or fluorescent in situ hybridisation (FISH) probes (Amann et al, 1990;Mobarry et al, 1996;Hovanec et al, 1998;Watanabe et al, 2001;Mohan et al, 2004;Geets et al, 2007;Smith et al, 2007). The PCR products were separated by electrophoresis on a 1% agarose gel and visualised by staining with 0.5 mg of ethidium bromide per mL of gel.…”
Section: Detection Of Nitrifying Bacteriamentioning
confidence: 99%
“…Previous PCRbased analysis of nrfA diversity in anammox and sulfate-reducing reactors showed that the majority of clones were most closely related to nrfA genes from Bacteroides spp. (40).…”
mentioning
confidence: 99%